Utilization of Communication Technology for Business - Lilis Puspitawati; A Nurhasanah; A S Khaerunnisa (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2021)
Advances in technology, computers, and telecommunications support the development of internet technology. Currently, the IT function in society has begun to change. Initially, the IT function as a means of exchanging electronic information to an application that is used to implement corporate business strategies such as marketing, sales, and customer service activities. The purpose of this study is to get empirical evidence of the benefits of using communication technology for business people. This research used a descriptive method by conducting a survey in the form of a questionnaire and conducting several further interviews. The results showed that using communication technology such as the Digital Platform can make it easier for sellers to market products and make it easier to interact with buyers. This research discusses that using communication technology such as the Digital Platform is one of the best business strategies. The conclusion obtained in this study is that the Digital Platform is the best solution to expand business networks and make it easier for sellers and buyers to make transactions. The benefit of doing this research is to find out the meaning and purpose of developing business communication by involving digital technology in marketing products or services.